Cyber-physical systems integration of building information models and the physical construction. Issue 5 (21st September 2015) - Professor Monty Sutrisna and Professor Mohan M. Kumaraswamy, Associate; Akanmu, Abiola; Anumba, Chimay J.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – In spite of the benefits of virtual models in the building and construction industry, the full potential of these models, especially in the construction and operation phases, remains largely unrealized. With the increasing developments in information and communication technology, a number of attempts have been made to extend the use of these models, through the development of integration approaches and technologies. However, the issue of integrating the virtual model and the physical construction such as to enable bi-directional coordination, has not been adequately addressed. Thus, the purpose of this paper is to investigate the application of a cyber-physical systems (CPS) approach in enhancing bi-directional coordination between virtual models and the physical construction. Design/methodology/approach – This research employs scenario development rapid prototyping to illustrate CPS integration in the construction industry, with a particular focus on facilitating bi-directional coordination. The proof-of-concept prototype systems developed were validated using a focus group consisting of industry practitioners. Findings – Bi-directional coordination between virtual models and the physical construction has the potential to improve real-time progress monitoring and control of the construction process, tracking of changes and model updates, information exchange between the design office and the job site, real-time documentation of the as-built status of high-value components and improved sustainability practices. Originality/value – This paper adds value to the construction industry by demonstrating the application of the CPS approach in enhancing bi-directional coordination between virtual models and the physical construction through the development of system architectures, scenarios and prototype systems.